Hsp70 Isoforms Are Essential for the Formation of Kaposi’s Sarcoma-Associated Herpesvirus Replication and Transcription Compartments - Baquero-Pérez, Belinda (PLoS Pathog, 2015)
Kaposi’s sarcoma-associated herpesvirus (KSHV) is an oncogenic herpesvirus associated with various AIDS-related malignancies. Like other herpesviruses, multiple processes required for KSHV lytic replication, including viral transcription, viral DNA synthesis and capsid assembly occur in virus-induced intranuclear structures, termed replication and transcription compartments (RTCs). Here we utilised a novel methodology, combining subcellular fractionation and quantitative proteomics, to identify cellular proteins which are recruited to KSHV-induced RTCs and thus play a key role in KSHV lytic replication. We show that several isoforms of the HSP70 chaperone family, Hsc70 and iHsp70, are redistributed from the cytoplasm into the nucleus coinciding with the initial formation of KSHV-induced RTCs. We demonstrate that nuclear chaperone foci are dynamic, initially forming adjacent to newly formed KSHV RTCs, however during later time points the chaperones move within KSHV RTCs and completely co-localise with actively replicating viral DNA. The functional significance of Hsp70 isoforms recruitment into KSHV RTCs was also examined using the specific Hsp70 isoform small molecule inhibitor, VER-155008. Intriguingly, results highlight an essential role of Hsp70 isoforms in the KSHV replication cycle independent of protein stability and maturation. Notably, inhibition of Hsp70 isoforms precluded KSHV RTC formation and RNA polymerase II (RNAPII) relocalisation to the viral genome leading to the abolishment of global KSHV transcription and subsequent viral protein synthesis and DNA replication. These new findings have revealed novel mechanisms that regulate KSHV lytic replication and highlight the potential of HSP70 inhibitors as novel antiviral agents.